Output comovement and inflation dynamics in a two-sector model with durable goods: The role of sticky information and heterogeneous factor markets - Tomiyuki Kitamura; Tamon Takamura (Bank of Canada, 2016)
In a simple two-sector New Keynesian model, sticky prices generate a counterfactual negative comovement between the output of durable and nondurable goods following a monetary policy shock. We show that heterogeneous factor markets allow any combination of strictly positive price stickiness to generate positive output comovement. Even if the prices of durable goods are flexible, adding sticky information ensures that the output of both sectors moves in the same direction. Furthermore, we find that the combination of sticky information and heterogeneous factor markets produces humpshaped responses in both sectoral output and inflation, as observed in a vectorautoregression analysis. In contrast to backward indexation to past inflation, which is often assumed in the literature, sticky information leads to a hump-shaped response in the inflation of flexibly priced goods. Finally, the estimated information stickiness through the minimum-distance estimation method suggests that information rigidity is stronger in residential investment than nondurable goods and services.
Keywords: E31; E32; E52; 330; Inflation and prices; Transmission of monetary policy